Analisis Manajemen Komplain terhadap Kualitas Pelayanan Kesehatan di Puskesmas Banda Raya Kecamatan Banda Raya Kota Banda Aceh - Sahla Nabila; Tahara Dilla Santi; Hanifah Hasnur (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Complaint management is an important element in improving the quality of health services, especially in health centers that act as the front line of public health services. Even though it has been ISO certified, the Banda Raya Health Center still receives complaints, such as long waiting times, inadequate health center facilities and the attitude of the officers. This study aims to analyze the management of complaints on the quality of health services at the Banda Raya Health Center, Banda Raya District, Banda Aceh City. The type of research used is qualitative research with a descriptive approach, and data analysis using Nvivo. The research subjects were taken using the purposive sampling technique. Data was collected through interviews, documentation, and observations. This research was carried out from December 18, 2024 to December 20, 2024. The results of the study show that the complaint management system is quite good with formal channels such as suggestion boxes, JKN applications, and social media, as well as structured recording and handling of complaints. However, there are still shortcomings in response speed and supporting facilities. The public prefers direct communication because it is considered more effective, even though the complaint process is easy. Research suggests that Puskesmas should increase the speed of response to complaints, improve patient support facilities, and improve the quality of direct communication to increase community satisfaction.